Pembuatan Prototype Smart Budidaya Ikan Mas Koki Berbasis Arduino - Dicky Abiyaksa; Setyono Hari Adi; Ridwan Siskandar (Jurnal Sains Indonesia, 2020)
An prototype of an arduino-based chef's goldfish smart prototype has been created which is able to feed fish automatically with a time reference stored in the RTC module. The pool water circulation process works by utilizing the condition of the pool water temperature read by the DS18B20 sensor. The LCD displays real time feeding information and water temperature values.